2022
DOI: 10.1002/marc.202200404
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Relationships of Shape Memory, Semicrystalline Polymers Fabricated by In Situ Polymerization and Crosslinking of Octadecyl Acrylate/Polybutadiene Blends

Abstract: The current work presents the study of a semicrystalline, shape memory polymer synthesized by simultaneous free radical polymerization and crosslinking in a blend of polybutadiene (PB) and octadecyl acrylate. Blending elastomers and phase change materials provide a modular method for new smart materials, such as shape memory polymers. In this system, grafted, side-chain crystalline poly(octadecyl acrylate) (PODA) fixes a programmed shape in the shape memory cycle, while crosslinked polybutadiene drives shape r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…This is done without any peroxide initiator and therefore avoids the potential hazards of working with peroxide-containing materials as examined in our previous work. 18,19 This present work follows the previous reports of Luchtenberg et al who showed the grafting of ODA to PB by an Alder-ene reaction. 23 They observed no gelation when they heated PB (M n = 1700 g/mol, 75 mol % 1,4-cis, 24 mol % 1,4trans, and 1 mol % vinyl) with ODA in the presence of N,Ndiphenyl-p-phenylenediamine, and acetylacetone in a dark reaction vessel under a nitrogen atmosphere at 180 °C for 25 h. However, in this current study, a higher MW PB (M n = 234,322 g/mol) was used where gelation occurs due to a thermally driven cross-linking reaction along with simultaneous ODA grafting of PB, resulting in a cross-linked graft network mixed with ODA crystals capable of exhibiting shape memory properties.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is done without any peroxide initiator and therefore avoids the potential hazards of working with peroxide-containing materials as examined in our previous work. 18,19 This present work follows the previous reports of Luchtenberg et al who showed the grafting of ODA to PB by an Alder-ene reaction. 23 They observed no gelation when they heated PB (M n = 1700 g/mol, 75 mol % 1,4-cis, 24 mol % 1,4trans, and 1 mol % vinyl) with ODA in the presence of N,Ndiphenyl-p-phenylenediamine, and acetylacetone in a dark reaction vessel under a nitrogen atmosphere at 180 °C for 25 h. However, in this current study, a higher MW PB (M n = 234,322 g/mol) was used where gelation occurs due to a thermally driven cross-linking reaction along with simultaneous ODA grafting of PB, resulting in a cross-linked graft network mixed with ODA crystals capable of exhibiting shape memory properties.…”
Section: Introductionsupporting
confidence: 90%
“…Figure 11b,c compares the shape memory properties of annealed PB-xODA (current study) and annealed PB-xPODA-yDCP samples (previous study using peroxide curing and using PB with a different molecular weight and higher 1,2 content 18 ). While a plateau is observed in the fixity at high ODA loading in the peroxide cured samples, a more continuous decrease is observed in annealed PB-xODA.…”
Section: X-ray Characterization Of Annealed Pb-xodamentioning
confidence: 87%
See 2 more Smart Citations
“…
shape changes in response to external stimuli, are a class of most important candidates for biomimetic smart materials. [7][8][9][10] According to whether the shape deformation was reversible, SMPs could be classified into one-way (1W-SMPs) and two-way SMPs (2W-SMPs). Considering that 2W-SMPs could perform reversible shape deformation between two distinct shapes back and forth without new programming, they were more suitable for realizing complex functions.
…”
mentioning
confidence: 99%